Genetic testing for hereditary breast and ovarian cancer susceptibility - Kozak, Agnieszka; Sielużycka, Joanna; Pronobis, Justyna; Ząbkowska, Katarzyna; Górnasiowa, Maria; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Breast cancer is the most frequently observed neoplasm in women around the Western World. In women aged 40 to 55, breast cancer is the leading cause of all mortality. There had been a dramatic increase in the incidence of breast cancer for several decades. Ovarian cancer accounts for 4% of all cancer diagnoses and 5% of all cancer deaths. The true hereditary predisposition of appearance of breast or ovarian cancers is noted between 5% to 10% all these diagnoses. The identification of the BRCA1 and BRCA2 genes has provided new insights into the understanding of breast and ovarian cancer genetics. Mutations of these genes markedly increase lifetime risk of developing breast cancer. Mutations in BRCA1 are associated with a 50% to 85% risk of developing breast cancer during a woman's lifetime, particularly at early age. The similar risk of breast cancer is related to BRCA2 mutations. In addition, BRCA1 mutations increase the risk of developing prostate and colon cancers, and BRCA2 mutations improve the risk of appearance of prostate and larynx as well as breast cancer in men. Three distinct clinical syndromes associated with hereditary ovarian cancer have been identified: 1) hereditary breast-ovarian cancer syndrome usually associated with mutations of the BRCA1 locus, 2) hereditary site-specific ovarian cancer syndrome, and 3) Lynch II syndrome. Genetic testing is indicated above all in: 1) young women with diagnosed breast or ovarian cancer, 2) women with familial history of breast and ovarian cancer, 3) mutations in BRCA1 and BRCA2 carriers' family members, and 4) men with diagnosed breast or prostate cancer and its relatives. Psychosocial impact of genetic testing is the important issue. Prior to undertaking this testing, it is rational to review how the patient may handle the results and to provide for psychiatric support should an adverse psychological outcome occur. Mutation carriers can be offered earlier and aggressive surveillance, chemoprevention with surveillance, or prophylactic surgery. For example, the women with an inherited susceptibility gene should perform monthly breast self-examinations, undergo a clinical breast examination once or twice a year, and have annual mammograms beginning between the ages of 25 and 35.